Development Of Parenting Modules For Parental Knowledge In The Prevention Of Sexual Orientation Deviations From An Early Age In Early Childhood - Fatchurrohmah, Luluk Mariyam; Sukiman, Sukiman (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2025)
This research aims to develop a parenting module as a strategy to prevent sexual orientation deviations from an early age in the PAUD Unit.  This module is designed to increase parents’ understanding of their role in shaping children’s gender identity healthily and by applicable social norms and cultural values.  This research uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model approach.  The study subjects were parents of early childhood who were in the PAUD Unit in Pondok Melati and Jatisampurna Districts, Bekasi City.  The results of the study show that many parents have limitations in understanding gender and sexuality issues and lack the skills to provide the proper education to their children.  Therefore, the parenting module developed in this study is focused on improving parental literacy through pocketbooks and parenting training.  The implementation of this parenting module shows a significant increase in parents’ understanding and readiness to guide their children.  In addition, this module has also received validation from early childhood education and psychology experts, who consider this approach relevant and can be applied in various family settings.